Education and science: current trends - Ledovskikh I. A., Zhulidova I. V., Turkina L. V., Romanchenko M. K., Gundyrev V. B., Koroleva E. N., Losev V. V., Morozova T. V., Chernyshev V. P., Isaev Y. N. (Education and science: current trends, 2019)
professions in the field of information technology today are almost the most popular. Therefore, school graduates, who have decided to enroll in these areas of training, choose Computer Science Exam as one of the USE exams. But the statistics on the performance of certain tasks by schoolchildren on specific topics is still low.
Keywords: основы алгебры логики; ЕГЭ по информатике и ИКТ; статистика выполнения заданий; рекомендации при подготовке школьников; fundamentals of logic algebra; USE in computer science and ICT; task execution statistics; recommendations when preparing schoolchildren